Pulsed Nd:YAG Laser Deposition Of Semiconducting And Transparent Indium-Tin-Oxide Anode For Organic Light Emitting Device - Yong, Thian Kok (2007)
The main objective of this work is to deposit device-quality ITO films by pulsed Nd:YAG laser for the operation of ORganic Light Emitting Device (OLED). It first requires parametric studies of ITO properties with the laser wavelength, target-to-substrate distance, the substrate temperature, and the background gas.